Resposta :
Explicação passo-a-passo:
a)[tex]3x+5=23[/tex]
[tex]3x=23-5[/tex]
[tex]3x=18[/tex]
[tex]x=\frac{18}{3}[/tex]
[tex]x=6[/tex]
b)
[tex]2x+10=18\\2x=18-10\\2x=8\\x=\frac{8}{2} \\x=4[/tex]
c)
[tex]5x+4-3x+10\\5x-3x+10+4\\ 2x+14[/tex]
d)
[tex]12x+6 = 5x-43\\12x=5x-43-6\\12x=5x-49\\12x-5x=49\\7x=-49\\x=\frac{-49}{7} \\x=-7[/tex]
e)
[tex]6x+9=3x-5\\6x=3x-5-9\\6x=3x-14\\6x-3x=-14\\3x=-14\\x=\frac{-14}{3}[/tex]
f)
[tex]2x-4 + 8/x\\\frac{2x + (8 - 4)}{x} \\\frac{2x + 4}{x} \\2 + \frac{4}{x} \\[/tex]